2022
DOI: 10.3389/fpsyg.2022.794258
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Chief Executive Officer Characteristics and Corporate Social Responsibility Reporting: Evidence From Chinese-Listed Firms

Abstract: Corporate social responsibility (CSR) strategy hinges largely on the CEO characteristics in the context of an emerging market. Based on a sample of 16,144 firm-year observations obtained from 1,370 unique Chinese-listed firms, which whether voluntarily issue CSR reports over the period 2008–2019, this paper empirically examined the impact of CEO characteristics on the likelihood of issuing CSR reports. We find that CEO age, MBA education, international experience and political ideology consciousness are positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…As individuals have different levels of education, their cognitive abilities, mindset and values may also differ significantly (Lu & Zhang, 2015; Saidu, 2019; Wang et al, 2022). Previous research has established that CEOs with higher levels of education have a longer‐term perspective and place greater emphasis on corporate sustainability (Ghardallou, 2022; Huang, 2013; Velte, 2020; Zhao, Wang, et al, 2022). Higher‐educated CEOs have more comprehensive insights and stronger logical thinking skills (Wang et al, 2022), which makes them more likely to consider the comprehensiveness and objectivity of sustainability reports and therefore work to improve the quality of the sustainability report texts.…”
Section: Institutional Background and Hypotheses Developmentmentioning
confidence: 99%
“…As individuals have different levels of education, their cognitive abilities, mindset and values may also differ significantly (Lu & Zhang, 2015; Saidu, 2019; Wang et al, 2022). Previous research has established that CEOs with higher levels of education have a longer‐term perspective and place greater emphasis on corporate sustainability (Ghardallou, 2022; Huang, 2013; Velte, 2020; Zhao, Wang, et al, 2022). Higher‐educated CEOs have more comprehensive insights and stronger logical thinking skills (Wang et al, 2022), which makes them more likely to consider the comprehensiveness and objectivity of sustainability reports and therefore work to improve the quality of the sustainability report texts.…”
Section: Institutional Background and Hypotheses Developmentmentioning
confidence: 99%
“…Hometown attachment as one of the psychological characteristics of executives is an important research branch on the antecedent causes of corporate social responsibility, and the focus of the upper echelons theory. Although related studies have focused on the association of CEO psychology with CSR engagement from different perspectives, such as Narcissism and cognitive style, and the influence of psychological factors embedded in life experiences, gender, and cultural background ( Du et al, 2014 ; Petrenko et al, 2016 ; Galbreath, 2018 ; Xu and Ma, 2021 ; Zhao et al, 2022 ), the mechanism how hometown attachment affects the performance of corporate donation is under-revealed. In a foundation of upper echelons theory, Hambrick and Mason (1984) suggested that “executive characteristics–corporate strategy–corporate financial performance” is a continuous process, and Grewatsch and Kleindienst (2017) also called for more attention to the moderating role of individuals in the CSR–performance relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extant studies based on the upper echelon theory have focused on the association of CEO psychology with CSR engagement from different perspectives, such as narcissism and cognitive style ( Li et al, 2020 ), and the influence of psychological factors embedded in life experiences, gender, and cultural background ( Du et al, 2014 ; Petrenko et al, 2016 ; Galbreath, 2018 ; Xu and Ma, 2021 ; Zhao et al, 2022 ). However, the mechanism of how hometown attachment affects the performance of corporate donation is under-revealed.…”
Section: Introductionmentioning
confidence: 99%
“…The research that explores the relationship between the characteristics of senior management teams and corporate CSR behavior is largely rooted in the altruistic theory [22]. According to this theory, personal moral development of entrepreneurs and the ethical culture prevailing within a company can directly influence the extent to which it engages in responsible business practices [23]. Such research generally assumes that the decision to fulfill or neglect CSR commitments is based on the values and beliefs of the individuals and the collective culture within the organization [24].…”
Section: The Status and Role Of Csrpsmentioning
confidence: 99%